2009
DOI: 10.4319/lo.2009.54.5.1413
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of detrital resources determines the outcome of competition between bacteria and a facultative detritivorous worm

Abstract: Macrobenthic deposit feeders and bacteria compete for the same detrital food resources. We hypothesize that the spatial scale at which food is distributed in the sediment is an important factor determining the outcome of this competition. Macrobenthic deposit feeders are better adapted for fast consumption of food in concentrated patches, whereas diluted food can only be exploited by bacteria. This hypothesis was tested in an experiment in which a fixed quantity of isotopically labeled algal detritus was offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Nevertheless, changes in bacterial feeding responses were attributed to differences in macrofaunal biomass across the OMZ. It has been shown experimentally that macrofauna feed more efficiently upon concentrated phytodetritus depositions than bacteria, making OM available to the microbial assemblages through excretion of faecal material (van Nugteren et al, 2009). Thus, stimulation of macrofaunal feeding responses may also result in retardation of phytodetrital C and N incorporation by the bacteria, consistent with increases in bacterial incorporation of phyto C and phyto N, which may be observed between 4 and 7 days.…”
Section: Methodological Considerationssupporting
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, changes in bacterial feeding responses were attributed to differences in macrofaunal biomass across the OMZ. It has been shown experimentally that macrofauna feed more efficiently upon concentrated phytodetritus depositions than bacteria, making OM available to the microbial assemblages through excretion of faecal material (van Nugteren et al, 2009). Thus, stimulation of macrofaunal feeding responses may also result in retardation of phytodetrital C and N incorporation by the bacteria, consistent with increases in bacterial incorporation of phyto C and phyto N, which may be observed between 4 and 7 days.…”
Section: Methodological Considerationssupporting
confidence: 53%
“…Lower macrofaunal biomass at this station (Table 1) may retard phyto N loss by remineralisation, potentially reducing faunalbacterial competition for the phytodetrital N source. This would allow increased niche differentiation between macrofaunal and bacterial assemblages (van Nugteren et al, 2009). We propose that macrofaunal activity makes OM available for bacterial utilisation and provides pathway for gradual phyto N loss.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…A notable exception to this pattern is the rapid macrofaunal response and retarded bacterial uptake of 13 C-tracer observed at 4850 m on the Porcupine Abyssal Plane, Northeast Atlantic, using an automated lander system (Witte et al, 2003). Rather than reflecting a unique response at the Porcupine Abyssal Plane, we suggest that this apparent discrepancy reflects the relatively large quantity of diatoms (83 mmol organic C m À2 ) administered in that study; macrofauna outcompete bacteria when accessing concentrated patches of organic resources and vice versa (van Nugteren et al, 2009). Contrary to our expectations, we found no evidence to suggest that substrate uptake into bacterial or macrofaunal biomass was affected by resource quality.…”
Section: Discussionmentioning
confidence: 68%
“…In other words, heterotrophic microbes and small and big animals compete for the same food. Van Nugteren et al (2009b) have shown that the spatial distribution of resources is a key factor governing the relative use of phytodetritus by bacteria vs. animals. Moreover, the relative share of organisms in the processing of organic matter was, in some systems and for some consumers, proportional to the biomass of the benthic size class, but not always (Moodley et al, 2005a;Woulds et al, 2009Woulds et al, , 2016.…”
Section: Ecologists Focus On the Dynamics Of Organisms Using Organic mentioning
confidence: 99%
“…This required substantial invest-ment in developing new methods: these studies basically revealed that predation on sedimentary bacteria was not that important (Kemp, 1990;Hondeveld et al, 1992;Hamels et al, 2001;Guilini et al, 2009). Van Oevelen et al (2006) conducted a detailed study on the fate of bacterial production using in situ 13 C labeling of bacteria. They observed that 8 % was lost by physical processes, 27 % was consumed by animal predation and bacterial mortality accounted for 65 %.…”
Section: Animal Stimulation Of Microbes: An Inverted Microbial Loop?mentioning
confidence: 99%